KAJIAN INDEKS KEBAHAGIAAN KOTA SEMARANG TAHUN 2018 - Etty Soesilowati; Dyah Maya Nihayah; Phany Inneke Putri (Jurnal Riptek, 2018)
During this time someone's happiness is identical with the material. In other words, the level of welfare is measured by the level of income. Actually, The level of community welfare can actually be measured in two ways, first, using the same standard (objective indicators)and second, unequal standards (subjective indicators). One of welfare indicators that measures achievement based on standards that are not the same for each individual is the Happiness Index. The research objective is to (1) find out how the Semarang City happiness index is in 2018; (2) to see how big is the difference of Happiness Index between people in Semarang City based on their level of education, gender, marital status, income, and length of stay. The main variables used in this study include material and immaterial aspects which include: (1) Household Income that represents individual work & income, (2) Condition of Houses and Assets, (3) Education, (4) Health, (5 ) Family Harmony, (6) Social Relations, (7) Availability of Leisure Time, (8) Environmental & Security Conditions, (9) Affection representing indicators of Achieved Desires/ Expectations & Life Satisfaction, (10) Life Happiness. The results showed that Semarang City Happiness Index in 2018 is 73.50. By gender, men are happier than women. From the level of education, the level of education of S2 and S3 is a group of citizens whose happiness index scores are always the highest. Citizens with married status are the happiest group. From the Income Level category, the happiest people are people with income of more than Rp. 7,200,000.00. The happiest groups of people are those who have lived for 21-30 years. This community group has an index value of 75.15. It turns out that the size of happiness in the city of Semarang is not only seen from a material size, but also obtained from the synergy with aspects of calm and tranquility of life. Therefore, the most important values in the determination of policies (regulation, planning policies, budgeting and finance or even development human resources and infrastructures policies) and The Government should concern on how to gain sustainability and conducive climate in formulating development programs, that can make community feel safe, comfortable, calm and peaceful.